Characterization of the absorption, metabolism, excretion, and mass balance of gefapixant in humans - Jesse C. Nussbaum; Azher Hussain; Bennett Ma; K. Chris Min; Qing Chen; Charles Tomek; Marian Iwamoto; S. Aubrey Stoch (Wiley, 2022)
Abstract Gefapixant (MK‐7264) is a first‐in‐class, selective antagonist of the P2X3 purinergic receptor currently being investigated as a therapeutic agent for the treatment of refractory or unexplained chronic cough. In non‐clinical studies, gefapixant was eliminated primarily by renal excretion of the parent drug. The objective of this study was to assess the disposition of gefapixant in humans. The absorption, metabolism, and excretion profiles of gefapixant were assessed after oral administration of a single dose of [14C]gefapixant to six healthy adult males. Following a single‐oral [14C]gefapixant dose to healthy adult males, the mass balance was achieved, with 98.9% of the administered radioactivity recovered in urine and feces. Elimination of gefapixant occurred primarily via renal excretion of the intact drug (64%); metabolism was a minor pathway of elimination of gefapixant (12% and 2% recovered in urine and feces, respectively). Single‐dose administration of [14C]gefapixant 50 mg was generally well tolerated in healthy adult males. The fraction of the anticipated therapeutic oral dose of gefapixant absorbed is estimated to be at least 78%. Gefapixant is expected to be the major circulating drug‐related material in plasma, and the majority of the dosed drug will be excreted unchanged in urine.